1979
DOI: 10.1093/ajcn/32.11.2233
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin pharmacokinetics in kwashiorkor

Abstract: Intravenous penicillin kinetics have been studied in eight children with kwashiorkor on admission to hospital and when rehabilitated. A 75% increase in penicillin clearance was observed with recovery, associated with a fall in half-life; this was probably due to an improvement of both renal plasma flow and tubular function. The present observations and those of other authors working in this area are discussed and an approach to drug dosage of renally excreted drugs in kwashiorkor has been proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 8 publications
0
28
1
Order By: Relevance
“…21,[26][27][28][29] Characteristics of pharmacokinetic studies are detailed in Table 3, Table 4 and Table 5. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] All included studies refer to children with SAM unless otherwise stated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,[26][27][28][29] Characteristics of pharmacokinetic studies are detailed in Table 3, Table 4 and Table 5. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] All included studies refer to children with SAM unless otherwise stated.…”
Section: Resultsmentioning
confidence: 99%
“…30,32,35 However, the side-effects of amoxicillin are predominantly idiosyncratic, with minimal dose-related toxicity.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…In the present study, it was found to be 123 + 72% in the acute phase of kwashiorkor and 109 + 11.6% on recovery; the reasons for high bioavailability values in this study are unclear. Previous data from this laboratory have shown that intramuscular penicillin bioavailability is unimpaired in kwashiorkor except in the presence of gross oedema (Buchanan, Robinson, Koornhof & Eyberg, 1979).…”
mentioning
confidence: 77%
“…Cl CU o described for penicillin (Buchanan Robinson et al, 1979) and for gentamicin (Buchanan, Davis & Eyberg, 1979 (Brogden et al, 1979), frequently by infusion over 20-30 min. This was not possible in the present study, due to the extreme difficulty of maintaining an i.v.…”
mentioning
confidence: 99%
“…1 in underweight patients (74) . Drug clearance is also reduced in PCM for chloramphenicol, penicillin, quinine and isoniazid (51,53,(75)(76)(77)(78) . The additive influence of acute infection on drug disposition may also play a distinct role (79,80) .…”
Section: Antimicrobial Examplesmentioning
confidence: 99%